Sustainability Report, Ukuran Perusahaan, dan Good Corporate Governance sebagai Determinan Kinerja Keuangan Perusahaan Makanan dan Minuman - Zuhri, Mustanwir; Utary, Devita Elyana (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2025)
The objective of this study to analyze sustainability reporting, firm size, and good corporate governance (GCG) as determinant of company’s financial performance measured by return on equity (ROE). GCG is proxied by the number of board commissioners, board of directors, and audit committee members. The objects of this research are food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. This study conducted under quantitative method by using data panel multiple regression technique. The data used are secondary data obtained from annual reports and sustainability reports published by the companies. The results show that sustainability repor has a negative effect on ROE, indicating that high levels of sustainability disclosure may reduce financial performance in the short term due to the high investment costs associated with sustainability initiatives. Firm size has a positive effect on ROE, suggesting that larger companies tend to achieve better financial performance caused by high efficiency. Conversely, the number of board directors has a negative effect on ROE, which may result from inefficiencies in the decision-making process. Meanwhile, the number of board commissioners and the audit committee does not affect ROE. This study suggests that not all aspects of governance and sustainability directly has impact on profitability.